2007
DOI: 10.1002/jmri.21186
|View full text |Cite
|
Sign up to set email alerts
|

MRI appearance of perianal carcinoma in Crohn's disease

Abstract: Detection of carcinoma in perianal Crohn's disease can be difficult. The purpose of this study was to describe the MRI appearance of anorectal cancer in patients with perianal Crohn's disease. A total of six patients with anorectal carcinoma (four mucinous adenocarcinoma, two squamous) in Crohn's disease were retrospectively reviewed. Axial T2 and dynamic postcontrast fat‐suppressed T1‐weighted gradient echo sequences were performed, and findings were compared with 18 noncancer patients with perianal fistulae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…To date, MRI has only been able to differentiate active from inactive perianal disease, but this imaging modality may be useful in differentiating benign from malignant change in PCD. 39 In this series, cancer was not diagnosed in any of the patients who had MRI preoperatively. However, a retrospective review of the MRIs revealed features that may be suggestive of cancer.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…To date, MRI has only been able to differentiate active from inactive perianal disease, but this imaging modality may be useful in differentiating benign from malignant change in PCD. 39 In this series, cancer was not diagnosed in any of the patients who had MRI preoperatively. However, a retrospective review of the MRIs revealed features that may be suggestive of cancer.…”
Section: Discussionmentioning
confidence: 91%
“…These features are irregular inner wall contours and delayed mild enhancement of internal tissues. 39 Among these six patients with cancer complicating PCD who were compared with controls without cancer, changes suggestive of cancer were present only in the cancer patients. Furthermore, a mucinous pattern was only found in the four cases of mucinous adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major role of MR imaging in the evaluation of perianal disease and for the staging of anal cancer is well established O'Malley et al, 2012;Schwartz et al, 2001;Torkzad and Karlbom, 2010;Horsthuis et al, 2009;Lad et al, 2007;Koh et al, 2008). In CD patient with anal or perianal carcinoma, MR imaging should be used to help guide surgeons for performing biopsies in suspicious areas (Torkzad and Karlbom, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In addition MR imaging allows differentiating between active and quiescent perianal disease (Koh et al, 2001) and assess response to therapy (Horsthuis et al, 2009). Although several authors have described the appearance of fistula-associated anal adenocarcinoma, the imaging appearance of anal cancer in CD patients has been reported scarcely (Devon et al, 2009;Lad et al, 2007;Yamaguchi et al, 2009;Yang et al, 2009;Tonolini and Bianco, 2013).…”
Section: Imaging Findingsmentioning
confidence: 98%